Allelic sequence variation in the Sub1A, Sub1B and Sub1C genes among diverse rice cultivars and its association with submergence tolerance - Singh, Anuradha; Singh, Yashi; Mahato, Ajay K.; Jayaswal, Pawan K.; Singh, Sangeeta; Singh, Renu; Yadav, Neera; Singh, A.K.; Singh, P.K.; Singh, Rakesh; Kumar, Rajesh; Septiningsih, Endang M.; et al. (Springer, 2020)
Erratic rainfall leading to flash flooding causes huge yield losses in lowland rice. The traditional varieties and landraces of rice possess variable levels of tolerance to submergence stress, but gene discovery and utilization of these resources has been limited to the Sub1A-1 allele from variety FR13A. Therefore, we analysed the allelic sequence variation in three Sub1 genes in a panel of 179 rice genotypes and its association with submergence tolerance. Population structure and diversity analysis based on a 36-plex genome wide genic-SNP assay grouped these genotypes into two major categories representing Indica and Japonica cultivar groups with further sub-groupings into Indica, Aus, Deepwater and Aromatic-Japonica cultivars. Targetted re-sequencing of the Sub1A, Sub1B and Sub1C genes identfied 7, 7 and 38 SNPs making 8, 9 and 67 SNP haplotypes, respectively. Haplotype networks and phylogenic analysis revealed evolution of Sub1B and Sub1A genes by tandem duplication and divergence of the ancestral Sub1C gene in that order. The alleles of Sub1 genes in tolerant reference variety FR13A seem to have evolved most recently. However, no consistent association could be found between the Sub1 allelic variation and submergence tolerance probably due to low minor allele frequencies and presence of exceptions to the known Sub1A-1 association in the genotype panel. We identified 18 cultivars with non-Sub1A-1 source of submergence tolerance which after further mapping and validation in bi-parental populations will be useful for development of superior flood tolerant rice cultivars.